(untitled) (Web of Teachers: Inderscience Research, 2025)
This article covers the content, significance of the integrative approach to the formation of moral education of preschool children, as well as the conditions for its implementation. The issues of organizing moral education in close connection with the processes of education, upbringing and development have been analyzed. On the basis of an integrative approach, the opportunities for the development of social behavior, spiritual and moral qualities in children are revealed.